The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.21522/tijar.2014.08.02.art007
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Disease Risk Among Patients with Type 2 Diabetes in Uganda

Abstract: While atherosclerotic cardiovascular disease risk is increased in patients with type 2 diabetes, the magnitude and socio-demographic determinants of this risk are not known in Uganda. We aimed to establish the magnitude of the predicted 10-year atherosclerotic cardiovascular risk and describe its socio-demographic determinants among patients with type 2 diabetes in Uganda. This was a cross-sectional study conducted in eight (8) diabetes clinics from November 2020 to February 2021. We enrolled 500 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…We have earlier shown that 65.8% of patients with T2D have a high 10 year predicted ASCVD risk 16 as determined with the Pooled Cohorts Risks Equation and the current study has shown that 56.4% of our patients have elevated AIP. The 10 -year predicted ASCVD risk assesses the global ASCVD risk i.e., coronary heart disease, ischaemic stroke and peripheral arterial disease risk while AIP is mainly a predictor of coronary artery disease 26 , which is the main cause of morbidity and mortality among the CVD spectrum in patients with T2D.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We have earlier shown that 65.8% of patients with T2D have a high 10 year predicted ASCVD risk 16 as determined with the Pooled Cohorts Risks Equation and the current study has shown that 56.4% of our patients have elevated AIP. The 10 -year predicted ASCVD risk assesses the global ASCVD risk i.e., coronary heart disease, ischaemic stroke and peripheral arterial disease risk while AIP is mainly a predictor of coronary artery disease 26 , which is the main cause of morbidity and mortality among the CVD spectrum in patients with T2D.…”
Section: Discussionsupporting
confidence: 63%
“…This was a cross-sectional study conducted in eight (8) diabetes clinics in Central-Uganda namely; Entebbe grade B hospital, Mengo Hospital, Naguru Hospital, Kasangati Health Center IV, Wakiso Health Center IV, Mpigi Health Center IV, Mityana Hospital and Kawolo Hospital. Detailed description of the methodology has been published elsewhere 16 . The study was approved by Mengo Hospital Research and Ethics Committee (Approval number MH/REC/100/9-2019) and was registered by Uganda National Council of Science and Technology (Registration number HS2738).…”
Section: Methodsmentioning
confidence: 99%